Lipid Composition and Antibacterial Screening of Lipophilic Extract of a Marine Sponge Haliclona sp. Collected from the Bay of Bengal (Orissa Coast), India - Manjari Mishra, Pravat; Sree, Ayinampudi (Asian Journal of Chemistry, 2011)
The fatty acid composition as well as volatiles and antibacterial screening of lipophilic extract of the sponge Haliclona sp. were analyzed. The fatty acids are characterized by linear saturated, short chain unsaturated, long chain unsaturated and long chain polyunsaturated fatty acids. Linear saturated fatty acids constituted 52 % of the total fatty acid content. An important polyunsaturated fatty acid (PUFA) i.e., linoleic acid was found to be 3.38 % of the total fatty acid content. The content of long chain fatty acids Δ5,9, was significant in Haliclona sp. (23.64 %). The antibacterial screening of the lipid extract of Haliclona sp. against different pathogens showed marked results.